Effects of phosphorus and aluminum levels on shoot and root systems of wheat - Zanatta, Ana Christina Albuquerque; Mundstock, Cláudio Mário (Pesquisa Agropecuaria Brasileira, 2014)
Two wheat (Triticum aestivum L.) genotypes (CNT 10 and PAT 7392) were grown under two phosphorus levels (40 and 160 ppm P2O5) and four lime levels (zero, 1/4, 1/2 and 1 SMP). Plants were grown in greenhouse and phytotron with controlled temperature, light and humidity. Both root dry weight and length were evaluated and also the shoot weight. Aluminum or low phosphorus affected growth and differentiation, reducing root length and dry matter production and increasing the shoot: root ratio. A compensation effect between Al and P was observed and its effects were stronger on the roots and CNT 10 characterizing a germplasm more tolerant to Al than PAT 7392.